The Mediating Role of Spiritual Well‐Being in the Relationship Between Spiritual Care Needs and Death Anxiety Among Coronary Intensive Care Patients - Ebubekir Kaplan; Cemile Hürrem Ayhan; Çağlar Şimşek; Mehmet Cihad Aktaş; Türkan İstek (Nursing in Critical Care, 2026)
ABSTRACT Background Patients hospitalised in coronary intensive care units often experience heightened existential distress, including increased spiritual care needs and death anxiety. Spiritual well‐being has been suggested as a key protective factor that may alleviate death‐related anxiety in critically ill populations; however, the mechanisms underlying these relationships remain insufficiently explored. Aims This study examined the relationships among spiritual care needs, spiritual well‐being and death anxiety in patients hospitalised in a coronary intensive care unit and tested whether spiritual well‐being mediates the relationship between spiritual care needs and death anxiety. Design A cross‐sectional design was employed. Methods The study included a convenience sample of patients hospitalised in a coronary intensive care unit in Eastern Turkey, between September and December 2024. Data were collected using a Sociodemographic and Clinical Variables Form, the Patients' Spiritual Needs Assessment Scale, the Functional Assessment of Chronic Illness Therapy–Spiritual Well‐Being Scale and the Templer Death Anxiety Scale. Data analysis involved descriptive statistics, Pearson correlation analysis and mediation analysis using Hayes's PROCESS macro (Model 4), with age and gender included as control variables. Results Patients reported moderate levels of spiritual care needs (3.04 ± 0.47), spiritual well‐being (30.53 ± 6.87) and death anxiety (8.04 ± 3.00). Spiritual care needs were positively associated with spiritual well‐being ( r = 0.56, p < 0.001) and its subdimensions (meaning, peace and faith). Death anxiety was negatively correlated with spiritual well‐being ( r = −0.32, p < 0.001), with the strongest association observed for the peace subdimension ( r = −0.39, p < 0.001). Mediation analysis demonstrated a significant indirect effect of spiritual care needs on death anxiety through spiritual well‐being ( b = −1.46, 95% CI [−2.28, −0.67]). Although higher spiritual care needs were directly associated with greater death anxiety, they were also associated with higher spiritual well‐being, which in turn was related to lower death anxiety, suggesting that spiritual well‐being may buffer the association between spiritual care needs and death anxiety. Conclusions Higher spiritual care needs among coronary intensive care patients are associated with greater spiritual well‐being, which in turn relates to lower levels of death anxiety. The significant indirect effect suggests that spiritual well‐being plays a buffering role in the relationship between spiritual care needs and death anxiety. Given the cross‐sectional design, these findings should be interpreted as associative rather than causal. Relevance to Clinical Practice Assessing spiritual care needs and supporting spiritual well‐being in coronary intensive care settings may be critical for reducing death‐related anxiety. Integrating spiritual care interventions—particularly those fostering inner peace and meaning—into routine nursing care may enhance holistic patient support and psychological resilience in critically ill patients.